Democracia digital e participação cidadã: um estudo de caso do governo do Estado do Rio Grande do Sul - Rotenberg, Marcelo Rabelo (2014)
The main aim of this work was to evaluate the digital participatory process pursuant to the second edition of the 'Governador Pergunta of Gabinete Digital'. For this aim, certain categories and criteria proposed by Villela (2012) were utilized who's objective are the evaluation of participant processes. The utilization of the mentioned criteria focuses on the concept of citizenship deliberaive, amplified by the edemocracy. These concepts include: discussion threads, pluralism, inclusion and common good. The data was collected, at first, by means of bibliographical research. Subsequently, interviews were conducted with the principal protagonists involved in the 'Gabinete Digital' and in the second edition of 'Governador Pergunta'. In summary, the results indicate the existence of spaces for discussion without decision making powers. Therefore, this active experience ensured to renew and highlight the public agenda in the state of Rio Grade do Sul and are means to improve the 'Gabinete Digital' and the tool that is the 'Governador Pergunta' in the public management.